On Art : Artists' Writings on the Changed Notion of Art After 1965. - de Vries, Gerd; André, Carl; Art & Language; Buren, Daniel; Burgin, Victor; Burn, Ian; Huebler, Douglas; Judd, Donald; Kosuth, Joseph; LeWitt, Sol; Morris, Robert; Ramsden, Mel; et al. (Schauberg : Verlag M. DuMont Schauberg Köln, 1974)
Andre, Carl ; Art & Language ; Buren, Daniel ; Burgin, Victor ; Burn, Ian ; Ramsden, Mel ; Huebler, Douglas ; Judd, Donald ; Kosuth, Joseph ; LeWitt, Sol ; Morris, Robert ; Roehr, Peter ; Weiner, Lawrence
Bibliog. p. 252-269
Duits
Engels
boek